ANALISIS PERENCANAAN PRODUKSI PADA PABRIK TAHU DI HILIGODU OMBOLATA - HERMAN WIJAYA MENDROFA; EKA SEPTIANTI LAOLI; NETTI KARIANI MENDOFA (LP2MTBM MAKARIOZ, 2022)
The purpose of this study was to analyze the production planning process at the tofu factory in Hiligodu Ombolata. What materials need to be provided in the production planning process at the Nias tofu factory? Tofu is one of the products of small and medium enterprises made from soybeans (Glycine Sp). This can be found in many areas. Starting from urban areas to rural areas, the tofu-making industry has begun to be developed. This study aims to solve any problems that become obstacles in the production planning process at the nias tofu factory, by using interview, observation and documentation methods, this is to provide benefits and facilitate the production planning process at the tofu factory.